Synthesis of Conjugated Copolymers Fluorene-based on Thieno-thiophene for Photovoltaic Cells - Mohd Sani Sarjadi; Yap Leong Khen; Mohd Hafiz Abd Majid; Sabrina Soloi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
Organic solar cells have been receiving more attention in the recent years due to the cost bottleneck cap of inorganic solar cells and the increasing demand for more low-cost renewable power sources. In this work, poly(9,9-didodecylfluorene-alt-thieno[3,2-b]thiophene), P1 composed of alternating fluorene based co-polymer unit was successfully prepared by direct arylation polymerization. P1 composed of alternating fluorene unit as a donor unit and thieno[3,2-b]thiophene as a donor unit which is a donor-donor co-polymer. The colour and phase of P1 were observed. TLC showed positive result for P1. The surface morphology of P1 was identified by SEM. The structure of P1 was confirmed by using 1H-NMR and 13C-NMR. Functional group present of P1 were identified by using FTIR. The λmax and range of adsorption of P1 were identified and band gap were calculated. The physical characteristics of P1 was compared and discussed. Based on the chemical characteristics, P1 has a high potential as organic photovoltaic material as UV-Vis shown a better adsorption range and lower band gap.